Psychosocial working conditions across working life may predict late-life physical function: a follow-up cohort study - Charlotta Nilsen; Ross Andel; Alexander Darin-Mattsson; Ingemar Kåreholt (BMC, 2019)
Abstract Background Increasing life expectancy has made understanding the mechanisms underlying late-life health and function more important. We set out to investigate whether trajectories of change in psychosocial working conditions are associated with late-life physical function. Methods Two Swedish surveys, linked at the individual level, were used (n = 803). A psychosocial job exposure matrix was used to measure psychosocial working conditions during people's first occupation, as well as their occupation every five years thereafter until baseline in 1991. Physical function was measured in 2014. Random effects growth curve models were used to calculate intraindividual trajectories of working conditions. Predictors of physical function were assessed with ordered logistic regression. Results A more active job at baseline was associated with increased odds of late-life physical function (OR 1.15, CI 1.01-1.32). Higher baseline job strain was associated with decreased odds of late-life physical function (OR 0.75, CI 0.59-0.96). A high initial level followed by an upward trajectory of job strain throughout working life was associated with decreased odds of late-life physical function (OR 0.32, CI 0.17-0.58). Conclusions Promoting a healthier workplace by reducing chronic stress and inducing intellectual stimulation, control, and personal growth may contribute to better late-life physical function.